NEW INNOVATIVE IDEAS IN THE FIELD OF PRODUCTION OF REINFORCED CONCRETE STRUCTURES - Bakhodir Rizayev, Islombek Akhmedov, Shavkat Yusupov, Isroiljon Umarov, Aleksandir Kazadayev, Farrukh Dadakhanov (Journals Park Publishing, 2022)
In many developed countries, instead of steel reinforcement in reinforced concrete, composite reinforcement is being used. The reason for this is that metal fittings cannot be used in aggressive environments. This material, composite reinforcement, is made using the latest achievements in chemistry and materials science, because it has unique properties. Composite fittings do not rot or rust under the influence of moisture.